2018
DOI: 10.1002/ajmg.c.31661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic heterogeneity in Dubowitz syndrome: Implications for diagnosis, management and further research

Abstract: Dubowitz syndrome was described in 1965 as a recognizable syndrome characterized by microcephaly, short stature, eczema, mild developmental delays, and an increased risk of malignancy. Since its original description, there have been over 200 reported cases though no single gene has been identified to explain a significant proportion of affected individuals. Since the last definitive review of Dubowitz syndrome in 1996, there have been 63 individuals with a clinical, or suspected, diagnosis of Dubowitz syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
(138 reference statements)
1
20
0
1
Order By: Relevance
“…The combined set of 7 novel candidate genes (Supplemental Table S2), 16 genes offering an alternative diagnosis (Table 2), and 8 DubS genes from the literature (Innes et al, 2018) exhibited significant PPI enrichment: 29 observed edges, 12 expected, PPI enrichment p ‐value = 4.5e‐05. The network, shown in Figure 2, captures four clusters: the two smallest clusters connecting our novel candidate genes to genes previously implicated in DubS under a recessive model: CDK11B to PCNT and VPS13B to UBE3B (Dieks et al, 2014; Innes et al, 2018); a second cluster driven by the genes within the chromosome X deletion observed in one case (note HDHD1 is another name for PUDP ); and a large cluster capturing many genes underlying syndromes similar to DubS and one of our novel candidate genes, TOP2A . This set of 27 genes is significantly enriched in 37 GO:Biological Processes (Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The combined set of 7 novel candidate genes (Supplemental Table S2), 16 genes offering an alternative diagnosis (Table 2), and 8 DubS genes from the literature (Innes et al, 2018) exhibited significant PPI enrichment: 29 observed edges, 12 expected, PPI enrichment p ‐value = 4.5e‐05. The network, shown in Figure 2, captures four clusters: the two smallest clusters connecting our novel candidate genes to genes previously implicated in DubS under a recessive model: CDK11B to PCNT and VPS13B to UBE3B (Dieks et al, 2014; Innes et al, 2018); a second cluster driven by the genes within the chromosome X deletion observed in one case (note HDHD1 is another name for PUDP ); and a large cluster capturing many genes underlying syndromes similar to DubS and one of our novel candidate genes, TOP2A . This set of 27 genes is significantly enriched in 37 GO:Biological Processes (Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the genes implicated by our analyses share biological pathways with each other and the genes underlying single gene disorders previously implicated in individuals diagnosed with DubS). The novel candidate genes, the genes driving alternative diagnoses among our cases and the genes implicated in the literature for individuals clinically diagnosed with DubS (Innes et al, 2018) were provided to STRING‐db (v11.0) (Szklarczyk et al, 2019) to assess for common pathways or interactions (Figure 1). This was performed by using human reference data, only the queried proteins, protein–protein interaction (PPI) data from known interactions (curated databases, experimentally determined), predicted interactions based on gene fusions and gene co‐occurrence, co‐expression, protein homology, and text mining; medium confidence (0.400) was the minimum required for interaction scores.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue of Seminars leads off with Dubowitz syndrome (MIM 223370), a condition first reported in 1965 and now reported more than 200 times (Dubowitz, ). In their research article, Innes, McInnes, and Dyment review the literature and provide evidence that both clinical and molecular/causal heterogeneity is likely the primary explanation why a major gene has yet to be identified for this disorder (Innes, McInnes, & Dyment, ). The same phenomenon is likely underlying the complexity of other recognizable conditions not included in this issue, including Toriello‐Carey syndrome (Toriello, Colley, & Bamshad, ), Fryns syndrome (Bone et al, ; Thompson & Cole, ), PEHO syndrome (Chitre et al, ), and 3C syndrome (Elliott et al, ; Kolanczyk et al, ).…”
Section: Themes Of the Issuementioning
confidence: 91%